2014
DOI: 10.1021/jp502317u
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on the Growth of High Edge Density Carbon Nanostructures: Transitions from Vertically Oriented Graphene Nanosheets to Graphenated Carbon Nanotubes

Abstract: Insights into the growth of high edge density carbon nanostructures were achieved by a systematic parametric study of plasma-enhanced chemical vapor deposition (PECVD). Such structures are important for electrode performance in a variety of applications such as supercapacitors, neural stimulation, and electrocatalysis. A morphological trend was observed as a function of temperature whereby graphenated carbon nanotubes (g-CNTs) emerged as an intermediate structure between carbon nanotubes (CNTs) at lower temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 32 publications
1
28
0
Order By: Relevance
“…Since then, several groups have explored the growth of VGNs on catalytic as well as non-catalytic metal / dielectric surfaces using various plasma based techniques such as microwave PECVD, dc plasma discharge, ICP-plasma and thermal plasma jet systems. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] In an excellent review, Bo et al 11 summarized the influence of various key process parameters on the synthesis and growth model for NGSs on various types of substrates. In spite of several existing reports, herein we note that, still there is no unique theory that could unveil the atomistic growth mechanism and give a prescription to optimize the process parameters for a given plasma source.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, several groups have explored the growth of VGNs on catalytic as well as non-catalytic metal / dielectric surfaces using various plasma based techniques such as microwave PECVD, dc plasma discharge, ICP-plasma and thermal plasma jet systems. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] In an excellent review, Bo et al 11 summarized the influence of various key process parameters on the synthesis and growth model for NGSs on various types of substrates. In spite of several existing reports, herein we note that, still there is no unique theory that could unveil the atomistic growth mechanism and give a prescription to optimize the process parameters for a given plasma source.…”
Section: Introductionmentioning
confidence: 99%
“…2(a) contains the highest density and the thinnest nanosheets of all the samples studied, indicating that the crystalline domain size is expected to be the smallest. TEM reported elsewhere [29] has shown that such structures terminate in few-layered graphene, down to two or three layers. The CNS structure in Fig.…”
Section: Resultsmentioning
confidence: 85%
“…It is intriguing that the nanocrystalline domain sizes are so similar for these samples, which could imply that FLG may nucleate at the sites of previously existing defects in support of the proposed nucleation and growth model for graphene foliates. [29,33] Interpretation of the nanocrystalline domain size calculation…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations